Students’ Perceptions of the Utilization of Artificial Intelligence in the Learning Process - Sudarmono Sudarmono; Maryanti Maryanti; asadiah Junita Dewi; Cici Cici (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to explore the perceptions of Economic Education students at Muhammadiyah University of Sampit regarding the utilization of artificial intelligence (AI) in the learning process. The integration of AI in higher education has become a global phenomenon that is transforming learning paradigms; however, understanding of how students evaluate and interpret this technology remains limited, particularly within the context of Economic Education in Indonesia. This study involved 15 students selected through purposive sampling and employed a descriptive qualitative approach grounded in the Technology Acceptance Model (TAM). Data were collected through semi-structured interviews and analyzed thematically using NVivo 12 Pro.The findings reveal that students perceive AI as enhancing learning effectiveness, being easy to use, and fostering academic motivation and independence. Four major themes emerged: perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention to use. The acceptance of AI was found to encompass not only technological dimensions but also social-emotional aspects. This study reinforces the relevance of TAM within the Indonesian higher education context and provides implications for developing ethical, creative, and adaptive technology-based learning policies aligned with students’ needs in the digital era.